2017
DOI: 10.1177/1362361317704421
|View full text |Cite
|
Sign up to set email alerts
|

Gaze to faces across interactive contexts in infants at heightened risk for autism

Abstract: Infant social-communicative behavior, such as gaze to the face of an interactive partner, is an important early developmental skill. Children with autism spectrum disorder exhibit atypicalities in social-communicative behavior, including gaze and eye contact. Behavioral differences in infancy may serve as early markers of autism spectrum disorder and help identify individuals at highest risk for developing the disorder. Researchers often assess social-communicative behavior in a single interactive context, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
(27 reference statements)
1
11
0
Order By: Relevance
“…Atypical face and eye processing has been linked to heightened risk of psychopathy (Bedford, Pickles, Sharp, Wright, & Hill, 2015) and autism spectrum disorders (ASD; Gangi et al, 2018;Shultz, Klin, & Jones, 2018). For example, newborns at risk for ASD are less attentive to faces, particularly direct-gaze faces, compared with low-risk newborns (Di Giorgio et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Atypical face and eye processing has been linked to heightened risk of psychopathy (Bedford, Pickles, Sharp, Wright, & Hill, 2015) and autism spectrum disorders (ASD; Gangi et al, 2018;Shultz, Klin, & Jones, 2018). For example, newborns at risk for ASD are less attentive to faces, particularly direct-gaze faces, compared with low-risk newborns (Di Giorgio et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…When examining dyadic constructs across outcome classifications, the most consistent or robust group differences are evident by 12–15 months [Gangi et al, 2018; Hutman et al, 2012; Kellerman et al, 2019; Ozonoff et al, 2010; Wan et al, 2013]. For example, Gangi et al [2018] reported infants who developed ASD engaged in less gaze to face behaviors during play at 12 months of age.…”
Section: Developmental Progress/outcome Comparisonsmentioning
confidence: 99%
“…When examining dyadic constructs across outcome classifications, the most consistent or robust group differences are evident by 12–15 months [Gangi et al, 2018; Hutman et al, 2012; Kellerman et al, 2019; Ozonoff et al, 2010; Wan et al, 2013]. For example, Gangi et al [2018] reported infants who developed ASD engaged in less gaze to face behaviors during play at 12 months of age. Similarly, Kellerman et al [2019] documented subclinical dyadic features of ASD evident during play by 15 months of age (i.e., lower infant and maternal responsiveness; lower joint engagement).…”
Section: Developmental Progress/outcome Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of prospective studies have reported data that make it more challenging to determine if regression has occurred. These include studies in which only standardized scores [Estes et al, ; Landa, Gross, Stuart, & Bauman, ; Levin, Varcin, O'Leary, Tager‐Flusberg, & Nelson, Lord, Luyster, Guthrie, & Pickles, ] or group data are reported [Barbaro & Dissanayake, ;Caravella & Roberts, ; Chenausky, Nelson, & Tager‐Flusberg, ; Filliter et al, ; Gliga, Smith, Likely, Charman, & Johnson, ; Ibañez, Grantz, & Messinger, ; Iverson et al, ], where loss and plateau are not differentiated [Brian et al, ], or where longitudinal analysis was not carried out [Bedford, et al, ; Gangi et al, ]. Although these studies show progressive divergence from typical development, they cannot differentiate developmental arrest or slowing from regression, and group data may have obscured variability within groups [Elsabbagh & Johnson, ].…”
Section: Evidence For Regression and Prevalence Ratesmentioning
confidence: 99%